2003
DOI: 10.1002/bdra.10096
|View full text |Cite
|
Sign up to set email alerts
|

Association between maternal fever and psychological/behavior outcomes: A hypothesis

Abstract: Much of the gestation/hyperthermia research has focused on the relationship between hyperthermia exposure and profoundly teratogenic outcomes. In this study we investigated subtler psychological/behavioral associations that may not be observable until later in development. Although the current study was hampered by technical limitations, the results support the need for more rigorously controlled research into a possible association between gestational fever and psychological/behavioral outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 32 publications
1
37
0
Order By: Relevance
“…In 3 studies on childhood autism 16,56 and autism spectrum disorders, 38 an increased risk was observed in relation to fever exposure. Increased risks were also reported for cerebral palsy, 15,49 developmental delay, 38 various behavior characteristics, 19 decreased academic performance, 19 and psychosis. 57 No overall association was reported for epilepsy 17 or schizophrenia, 21 however.…”
Section: Fever and Health Effects In The Childmentioning
confidence: 97%
See 1 more Smart Citation
“…In 3 studies on childhood autism 16,56 and autism spectrum disorders, 38 an increased risk was observed in relation to fever exposure. Increased risks were also reported for cerebral palsy, 15,49 developmental delay, 38 various behavior characteristics, 19 decreased academic performance, 19 and psychosis. 57 No overall association was reported for epilepsy 17 or schizophrenia, 21 however.…”
Section: Fever and Health Effects In The Childmentioning
confidence: 97%
“…Whether exposure later in pregnancy is harmful was less studied. Both the studies by Dombrowski et al 19 and by Calvani et al, 53 however, suggest that exposures in middle and late pregnancy may lead to longer-term adverse effects in the child. Nevertheless, the current evidence is insufficient to conclude whether fever might be harmful in all stages of pregnancy.…”
Section: Figurementioning
confidence: 99%
“…Epidemiological evidence, for instance, indicates higher incidences of psychopathologies, including schizophrenia, negative emotionality and panic disorders in children exposed to viral or bacterial infections in-utero [1], [2] or in early life [3]. Animal models that have been utilised to examine the impact of immune activation in early life have repeatedly demonstrated that exposure to bacterial or viral agents including mimetics (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Other prominent defects are seen in craniofacial development, such as facial clefts [103], the skeleton [104], the body wall, teeth, and heart [105]. Hyperthermia in utero [due to maternal influenza for instance] was long known to potentially induce structural anomalies in the fetus [106][107][108] but it has been described also as an environmental risk factor for psychological/behavioral disturbances [109] and, more particularly, schizophrenia [107]. It is stressed that these are not ultrasound-induced hyperthermia effects.…”
Section: Fetal Susceptibility To External Insultsmentioning
confidence: 99%